Ollieopteryx, a new genus of caddisflies from Madagascar (Trichoptera: Dipseudopsidae) - Weaver, John S.; Gibon, François-Marie; Chvojka, Pavel; Oláh, János (Zootaxa, 2020)
New taxa of Dipseudopsidae from Madagascar are described, including a new genus, Ollieopteryx, and three new species, Ollieopteryx fianarana, O. inopinata, and O. dakshan. The hypothetical phylogenetic tree of the Dipseudopsidae (Weaver & Malicky 1994) is revised to include Ollieopteryx, an isolated relic. Scenarios on the historical biogeography of the family are hypothesized.